KOMUNIKASI INTERPERSONAL PENDERITA NOMOPHOBIA DALAM MENJALIN HUBUNGAN PERSAHABATAN (Studi Pada Mahasiswa Ilmu Komunikasi di Universitas Riau) - Fitri Hardianti; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The trend in mobile phone use excessive negative impact on the individual who called syndrome No Mobile Phone Phobia (Nomophobia). Syndrome is one of the triggers rift in interpersonal relationships within friendship groups. This study aims to determine the patient interpersonal communication contact nomophobia on stage, stage of involvement, familiarity stage, the stage of decline, recovery and termination phase.This study uses a qualitative method. The collection of data obtained through observation, interviews, and documentation. The informants were 10 people consisting of 5 Top informant Namely those patients Nomophobia and 5 informants supporters of the companions of people with Nomophobia. were selected using purposive technique. This study uses data analysis techniques Miles and Huberman interactive. Mechanical data validity checking is done through the extension of participation and triangulation.The results showed that in interpersonal communication that occurs in patients nomophobia the friendship group is known at this stage of the contact, the communication process begins because of similarities in the nature, interest in the attitude, accident and needs of the partner or other person. At this stage of the engagement process takes place in the form of interpersonal communication did penchant together, and began to increase the frequency of meetings. At this stage of intimacy, communication process that takes indicated by own openness to one another and begin to tell you things that are both in the privacy of mobile phone or something beyond that. At this stage of deterioration, because the cause of the patient nomophobia not able to manage well the attitude of dependence so influential in friendship relationships. At this stage of improvement, here are clearly visible efforts made in order to maintain friendly relations, the effort can be a satire and a warning to patients nomophobia besides the efforts made also in the form of a mutual understanding of each other. The last stage which is the stage of termination, the study found no friendship is dismissed because they prefer to maintain and improve the relationship.Keywords: Interpersonal Communication, Patients of Nomophobia, Friendship